The effect of bark stripping by deer (Cervus elaphus L.) on biometric parameters of the scots pine (Pinus sylvestris L.) - Sporek, Monika; Sporek, Kazimierz; Ziembik, Zbigniew; Stebila, Ján; Kučerka, Martin; Lee, Seng Hua (Multidisciplinary Digital Publishing Institute, 2022)
Bark stripping by red deer (Cervus elaphus L.) is one of the most acute instances of damage wrought by these animals in a forest. Because of its location, bark stripping causes damage to the thickest and most valuable part of the tree trunk, which lowers the quality of the wood due to technical flaws. The research was conducted in 25 sampling sites of pine stands aged 35 years in a mixed, fresh forest habitat in south-western Poland. The study was aimed at assessing the influence of bark damage by deer on biometric parameters of pine stands (Pinus sylvestris L.). The assessment involved the diameter at breast height, height, basal area and volume of the tree stands. The results revealed a strong deer-specific pressure on the analysed pine stands. The share of bark stripped trees ranged from 65% to 96%. The number of bark damage instances (NBDI) on a given tree was found to significantly affect its diameter at breast height. The strip-damaged trees had breast height diameters lower by 23% on average, and their mean height was lower by 8.7% as compared with the trees without damage. The mean reduction in basal area increments (G1.3) of the trees was identified at 39%. In a similar way to the diameter at breast height and the basal area, the losses in tree stand volume growth caused by deer stripping were significant and oscillated at 41%.